(untitled) (Research in Agriculture Livestock and Fisheries, 2017)
Chronic respiratory disease (CRD) is one of the most important veterinary diseases in Bangladesh and all over the world. Mortality, reducing of weight gain and increasing of feed conversion ratio (FCR) are caused by CRD. Several drugs are used for prevention and control of Mycoplasmosis. It is caused by Mycoplasma gallisepticum (MG). Tylosin and Tiamulin are effective on M. gallisepticum. By considering generating resistance against antibiotics that is effective on MG, studying the effect of these drugs in the treatment and prevention of Mycoplasmosis in birds were the purpose of this research. In this study, 36 layer birds (MG positive) of 25 weeks aged divided in three similar groups (A, B and C) contain 12 birds in each group. In group A; Tylosin was administered after mixing with 2.5 gm in 1 L drinking water, for Group B; Tiamulin was administered after mixing with feed @ 0.45gm/kg feed and Group C; Control (No antibiotic was given, only common feeding). The Serum Plate Agglutination (SPA) test was conducted; in positive cases granules were formed slowly which could be seen during rocking. In the negative case, no such granules were formed. Overall 6 and 9 serums shown negative SPA test in Group A and Group B, respectively. Therefore, the efficacy of Tylosin was 50.00% and the Tiamulin was 75.00% which resemble statistically significant (P<0.05). In control group, 5 birds were died during experiment. It can be concluded that usage of these antibiotics especially Tiamulin can be essential in the treatment and prevention of Mycoplasmosis in birds. Res. Agric. Livest. Fish.4(3): 187-191, December 2017